Perumusan Konsep Kebijakan Peningkatan Kualitas Sentra Industri Mikro dan Kecil Kota Blitar - Gunarianto, Gunarianto (Jurnal Aplikasi Manajemen, 2008)
This research is aimed formulating quality increase of policy concept of micro and small industry centre located in Blitar city. Contribution of this research is expected to able to create the above quality increase of policy concept of micro and small industry centre located in Blitar city. Research method used is survey method, using Participatory Research Appraisal (PRA), Focus Group Discussion (FGD), processed by Structural Equation Modelling and SWOT analysis. Results of empirical analysis show that instituonalization significantly has a positive influence upon marketing, production, human resource and finance, each of with has, coeficients of 0,524, 0,471, 0,361 and 0.495. And, infrastructure factor having dominant influence upon human resource (0,472), followed by marketing (0,289), finance (0.276). Internal factor having significant influence upon working performace is marketing and production, each of with has coefficient of 0.547 and 0.128. This research implies that commitment and sinergy from all related sides is needed to succeed formulation result of general model development of micro and small industry centre located in Blitar city so that it will be successfully implemented.